2021
DOI: 10.1161/jaha.120.018248
|View full text |Cite
|
Sign up to set email alerts
|

Noncontrast Computed Tomography Markers as Predictors of Revised Hematoma Expansion in Acute Intracerebral Hemorrhage

Abstract: Background Noncontrast computed tomography (NCCT) markers are the emerging predictors of hematoma expansion in intracerebral hemorrhage. However, the relationship between NCCT markers and the dynamic change of hematoma in parenchymal tissues and the ventricular system remains unclear. Methods and Results We included 314 consecutive patients with intracerebral hemorrhage admitted to our hospital from July 2011 to May 2017. The intracerebral hemorrhage vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
1
19
1
Order By: Relevance
“…15 Previous studies have established that IVH growth (an increase of IVH volume by comparing the initial and follow-up CTs or as a delayed development of IVH on subsequent CT) is intimately tied to the with patients' neurological outcomes. 4,5 Yogendrakumar et al 6 also proposed that the definition of RHE exhibit diagnostic accuracy in the prediction of worse outcome superior to the conventional definition of hematoma expansion. These studies collectively indicated that recognition of RHE is an important step toward precision medicine for treatment target with the potential to improve outcomes in patients with ICH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Previous studies have established that IVH growth (an increase of IVH volume by comparing the initial and follow-up CTs or as a delayed development of IVH on subsequent CT) is intimately tied to the with patients' neurological outcomes. 4,5 Yogendrakumar et al 6 also proposed that the definition of RHE exhibit diagnostic accuracy in the prediction of worse outcome superior to the conventional definition of hematoma expansion. These studies collectively indicated that recognition of RHE is an important step toward precision medicine for treatment target with the potential to improve outcomes in patients with ICH.…”
Section: Discussionmentioning
confidence: 99%
“…3 Accumulating investigations have demonstrated that the inclusion of IVH growth into the conventional definition of hematoma expansion, that is, revised hematoma expansion (RHE), can boost the predictive accuracy of outcomes in patients with ICH. [4][5][6] Recently, an indicator termed the frequency of imaging markers (FIM) has been proposed for the prediction of hematoma expansion with better performance. 7 It is not clear whether the FIM can be used in predicting IVH growth or RHE.…”
Section: Introductionmentioning
confidence: 99%
“…Regions of interest (ROIs) were delineated by using Analyze 11.0 Software and ITK-SNAP 3.8.0 Software [10,11]. HE and revised HE were both calculated as previously reported [12]. All NCCT markers were rated on axial NCCT images for the following nine markers, namely (1) irregular (IRR) shape, (2) satellite sign, (3) island sign, (4) heterogenous (HET) density, (5) swirl sign, (6) black hole sign, (7) blend sign, (8) fluid sign, and (9) hypodensities, using definitions proposed by the International NCCT Study Group (Supplementary Materials Table S1) [4,5,[13][14][15][16][17][18][19][20][21].…”
Section: Image Analysismentioning
confidence: 99%
“…Many markers based on computerized tomography (CT) are increasingly used for predicting hematoma enlargement (HE), ICH prognosis, and perihematomal edema (PHE), such as black hole signs, blend signs, and island signs [ 8 , 9 ]. Several studies recently suggested that ICH patients with subarachnoid extension of hemorrhage (SAHE) seemed to have unfavorable outcomes [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%